Influence of Binder Types and Temperatures on the Mechanical Properties and Microstructure of Cemented Paste Backfill - Zhaowen Du; Shaojie Chen; Sheng Wang; Rui Liu; Dehao Yao; Hani S. Mitri (Advances in Civil Engineering)
In order to study the influence of burial depth or fire on the core area of cemented paste backfill (CPB), the experiment of CPB with different types of binder and temperature was carried out. Three types of binders, red mud (RM), Portland cement (PC), and slag cement (SC), are used and tested at 20°C, 40°C, 60°C, and 80°C. The macroperformance and microstructural evolution of CPB are analyzed using slump, uniaxial compressive strength (UCS), X-ray diffraction, and scanning electron microscopy (SEM). The results show that the coupled effects of binder type and temperature have a significant impact on the macroscopic performance and microstructural evolution of CPB. The CPB slump prepared with three types of binder meets the production requirement of the mine. Regardless of curing temperature and curing time, the uniaxial compressive strength of CPB samples with PC and SC is much higher than that of CPB samples with red mud. When cured for 12 hours, the uniaxial compressive strength of CPB samples containing PC and SC increases first, then decreases, and finally increases again with the increase of temperature. However, with the increase of temperature, the uniaxial compressive strength of CPB samples containing RM only increases first and then decreases. When the curing temperature is less than 40°C, the main reason for the increase in UCS was attributed to the fact that the temperature increase accelerates the hydration reaction and improves the density of the sample. When the curing temperature is 60°C, the main reason for the decrease in UCS is the formation of the expansive ettringite (AFt) which destroys the internal spatial structure of the sample. When the curing temperature is 80°C, the UCS increases again due to the fact that such high temperature can destroy the crystal structure of AFt and harden the hydration product C-S-H gel.